Online Brazilian Journal of Nursing is a resource for authors - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The Online Brazilian Journal of Nursing is delighted to receive articles for publication in all of these categories from nurses and others health professionals